Initial Modelling of Bird Strike by Numerical Simulation in Varied L/D Ratio of Bird Geometry - Yuniarti, Endah; H, Simon Shindu; Sitompul, Sahril Afandi (Institut Teknologi Dirgantara Adisutjipto, 2018)
This research studies influence of bird geometry on impact pressures during bird strike, namely Hugoniot and Stagnation pressure through initial modelling by numerical simulations. Bird geometry is capsule or cylinder with hemisphere end. The geometry is simulated with different L/D ratio, 1.4, 1.6, 1.8 and 2.0. Elastic-plastic hydrodynamic material model is used in simulation. Bird model simulation are using lagrangian method and initial velocities are 200 m/s. The results show variation of L/D ratio provide Hugoniot pressure 10-19 times higher than stagnation pressure in L/D = 1.4, 8-18 times in L/D = 1.6, 9-17 times in L/D = 1.8 and 4-16 times in L/D = 2. Hugoniot pressures show higher in ratio L/D = 1.8 and lower in ratio L/D = 1.6. Stagnation pressure show higher in ratio L/D = 2.0 and lower in ratio L/D 1.4.